Cytotoxicity of hantap (Sterculia oblongata Mast) leaves extracts against breast cancer cell line (T47D): effect on apoptosis and caspase-3 mRNA expression - Adika Suwarman; Indwiani Astuti; Woro Rukmi Pratiwi; Sitti Ayu Suhartina Yahya (Indonesian Journal of Pharmacology and Therapy, 2024)
Hantap (Sterculia oblongata Mast) leaves has been traditionally used in Palu, Central Sulawesi to treat breast cancer. However, its scientific evidence is limited. This study aimed to investigate the cytotoxicity of hantap leaf extracts against T47D breast cancer cells. The apoptotic activity of the extracts and its effect on caspase expression were also evaluated. The extracts were prepared by multilevel maceration using n-hexane, methanol, and water. Cytotoxic activity was evaluated by MTT assay. The apoptotic activity was observed by using a fluorescence microscope after acridine orange-propidium iodide (AO/PI) staining, whereas the caspase-3 mRNA expression was examined by using RT-PCR. Among the 3 tested extracts, the methanol extract exhibited the highest cytotoxicity with an IC50 value of 85 μg/mL. The methanol extract at concentrations of 42.5 μg/mL (½IC50), 85 μg/mL (IC50), and 170 μg/mL (2IC50) induced 127.25, 85.50, 479.5% of cell apoptosis, respectively. Furthermore, the methanol extract at concentrations of ½IC50, IC50, and 2IC50 increased 1.04, 1.43 and 1.69 time higher of caspase-3 mRNA expression. In conclusion, the methanolic extract of hantap leaf exhibits cytotoxicity against T47D breast cancer cells, by inducing apoptosis and increasing caspase-3 mRNA expression.